Gender distribution in authorship on research submissions at the European College of Veterinary Surgeons Annual Scientific Congress: 2012–2022 - Kathryn Pratschke; Kelly Blacklock; Alina Paczesna; Ishita Parakh; Jill R. MacKay; Fiona Mackay; Poppy Bristow (PLoS ONE, 2026)
The objective of this study was to explore gender distribution for authors on research presentations at European College of Veterinary Surgeons (ECVS) Annual Scientific Meetings from 2012–2022. Our populations for data collection included the ECVS Diplomate membership and authors listed for research submissions at the ECVS Annual Scientific Meetings between 2012–2022. Data was extracted from Conference Programs including year, first, second and senior (last) author names, and session type (scientific poster, short communication, resident forum). Authors were assigned a binary gender using a web-based algorithm to determine gender by first name. Gender demographics for ECVS Diploma holders between 1993–2023 was obtained from the ECVS Office for comparison to assess gender representation proportional to the specialty organisation, again this was based on a binary gender archetype. Although there are limitations to this approach, it is consistent with methodology in contemporaneously published papers in the human medical and veterinary fields. We identified 1353 research presentations, of which 1292 had complete information for all authors. At first author, men and women approached parity, but second and senior authors were more commonly men with the discrepancy being most marked at senior author level, and in the resident forum. If the first or senior author was a man, it was significantly more likely the second author would also be a man. There were no changes in authorship trends across the decade evaluated. In conclusion, women approached parity for first author but were under-represented as second and particularly senior author. In veterinary medicine, credit researchers receive is typically based on their position in the author list. First and senior author are more valued positions, with senior author usually having ownership of the project. Second author is the most valuable of the junior co-author positions but carries lower prestige than first or senior author. Further research is required to investigate underlying reasons contributing to ongoing gender disparity at senior author.